LEMBAGA PERWATIN DAN KEPUNYIMBANGAN DALAM MASYARAKAT ADAT LAMPUNG: ANALISIS ANTROPOLOGIS - Irham, Muhammad Aqil (Universitas Islam Negeri Raden Intan Lampung, 2013)
The indigenous society of Lampung is divided into two large groups; Saibatin and Pepadun. Both societies has many diversities in origins, so the local government arrangements is stimulated in the consultative mechanism represented by punyimbang at each level within the representative agency called Perwatin ( Proatin ). With anthropologic analysis , this paper would like to emphasize the meaning , role and function of institutional of Perwatin and Kepunyimbangan for indigenous peoples of West Lampung, its relevance to contemporary of democratic values, and the opportunities and the existence of the traditional institutions in the implementation of the reform of Regional Autonomy Law . According to the findings of the research, prowatin and punyimbangan are still very important to be implemented in local communities in West Lampung. This is case due to democratic values and local wisdom in prowatin institutions and kepenyimbangan accordance with the conditions of the community and institutional environment in which it arise.